ANALISIS KEMAMPUAN NUMERASI SISWA DALAM PEMBELAJARAN MATEMATIKA DI SMPN 27 BANDAR LAMPUNG - Rifka Ayu Anggia; Tommy Ardiansyah; Yola Arjunita Putri; Sintya Eka Wahyuni; Yetri; Junaidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to describe the numeracy skills of SMPN 27 Bandar Lampung students who have low, medium, and high numeracy skills in number domain, algebra, and geometry. This research approach is qualitative with case study method. This research was conducted at SMP Negeri 27 Bandar Lampung located at Jl. Raya Puri Gading, Sukamaju, Kec. Teluk Betung Timur, Bandar Lampung City. The primary source of this research is the principal and education personnel in the marketing department. While secondary sources in this study are books, documents, and scientific articles related to the research. Data collection techniques using observation interviews and documentation. Test the validity of the data using data triangulation. And data analysis using Miles and Huberman analysis techniques, namely by codifying data, presenting data, and drawing conclusions. The results of the research prove that: students with low numeracy skills are generally able to use a variety of numbers and symbols related to basic mathematics to solve problems in various contexts. Students with medium and high numeracy skills generally have numeracy skills, namely: (1) able to use various kinds of numbers and symbols related to basic mathematics to solve problems in various contexts; (2) able to analyse information displayed in various forms; and (3) able to use interpretation of analysis results to make decisions.